The EU Habitats Directive in Spain: can it contribute effectively to the conservation of extensive agroâ€ecosystems? - Beaufoy, G. (Journal of Applied Ecology, 1998)
1. By adopting the Habitats Directive (Directive 92/43 of 21 May 1992 on the con- servation of natural habitats and of wild fauna and flora) in 1992, the governments of the European Community committed themselves to the creation of the Natura 2000 ecological network, with the aim of conserving an extensive range of European habitat types and wildlife species. In doing so, they set in motion the most significant initiative for nature conservation in the history of Europe. 2. In Spain, Natura 2000 will have a considerable impact on the conservation of habitats and species, potentially increasing the percentage of national territory within protected areas from 6% to as much as 20%. 3. This paper aims to illustrate the importance of extensive farming systems to the maintenance of habitats within Natura 2000, and vice versa.
Keywords: Biodiversity; European policy; Extensive farming; policy instruments.

The EU Habitats Directive in Spain: can it contribute effectively to the conservation of extensive agroâ€ecosystems? - Beaufoy, G (Journal of Applied Ecology, 1998)
1. By adopting the Habitats Directive (Directive 92/43 of 21 May 1992 on the con- servation of natural habitats and of wild fauna and flora) in 1992, the governments of the European Community committed themselves to the creation of the Natura 2000 ecological network, with the aim of conserving an extensive range of European habitat types and wildlife species. In doing so, they set in motion the most significant initiative for nature conservation in the history of Europe. 2. In Spain, Natura 2000 will have a considerable impact on the conservation of habitats and species, potentially increasing the percentage of national territory within protected areas from 6% to as much as 20%. 3. This paper aims to illustrate the importance of extensive farming systems to the maintenance of habitats within Natura 2000, and vice versa.
Keywords: Biodiversity; European policy; Extensive farming; policy instruments.